Mastering Qt 5 : create stunning cross-platform applications using C++ with QT Widgets and QML with QT Quick /: create stunning cross-platform applications using C++ with QT Widgets and QML with QT Quick. (2018) - Lazar, Guillaume; Penea, Robin
No abstract available